Adaptive second order sliding mode control of an oscillating water column - Mosquera, Facundo (2024)
The energy from waves has a vast untapped potential to contribute to renewable energy supply and diversification. For that reason, wave energy conversion systems have been a topical research area in recent years. In particular, harnessing wave energy with an oscillating water column converter has proved to be one suitable solution, which has also seen a number of successful deployments. Nevertheless, additional research is required for this technology in order to reach full commercial maturity and economic performance. This paper proposes an adaptive second order sliding mode controller to maximise the converted energy. In particular, the proposed adaptive control setup maintains the sliding mode robust features, while reducing high frequency oscillations and abrupt control actions produced by fixed-gain algorithms. A comparison of energy generation performance shows better energy conversion efficiency of the proposed control strategy over standard speed regulation control strategies, even considering air compression dynamics and hydrodynamics in the tests.